Criminal Law Enforement Towards Journalists That Spread False News - Rizky Efriliandis (Faculty of Law, Universitas Lampung, 2021)
The press in performing its functions can not be separated from all acts of fraud and irregularities committed by the subjects of the press both the public, the press (journalists, media, press council, etc.), even the government. Criminal law has two main elements namely, the first is the existence of a norm, which is a prohibition or order (rule). Second, the existence of sanctions for violations of the norm in the form of threats with criminal law. This research aims: 1) to analyze criminal law enforcement against journalists who make the wrong coverage. 2) To analyze the legal liability system for journalists who make the wrong coverage. 3) To analyze the efforts that can be taken due to wrong press reporting. the research method used is qualitative analysis, data sources obtained through interviews, observations, documentation and literature relating to the title of the study. If the elements of crime committed by journalists are fulfilled egal liability mechanism for journalists who make the wrong reporting, then the legal liability is resolved through the mechanism of the Press Law by referring to the Press Council as the party authorized by law. Enforcement of criminal law against journalists who make scientific publications are based on journalists that have violated provisions which are guidelines for writing news an caused impact on parties who are disadvantaged by the publication. Efforts that can be taken as a result of wrong press reporting can be done by making complaints at the Press Council which will resolve public complaints on cases related to press reporting to immediately revoke, rectify, and correct false and inaccurate news accompanied by an apology to the reader, listener, and or viewer.There is an urgency for control by the Head of Newspapers in applying the journalistic code of ethics to journalists is carried out continuously. Moreover, the journalistic code of ethics needs to be a guideline for conducting news breeding. To the public, they should not hesitate to report to the Press Council if there is false publication of the news.